Penyelesaian Status Tanah Hak Milik yang Berada dalam Kawasan Hutan Produksi yang Dapat Dikonversi (HPK) di Kabupaten Indragiri Hulu Provinsi Riau - Almas Fadhil Ramadan; Akhmad Budi Cahyono (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
This study aims to discuss the status of Freehold land located in the convertible production forest area (HPK) in Indragiri Hulu Regency, Riau Province. In Riau Province, there was a determination of forest areas which resulted in Freehold land being included in the forest area. This caused Freehold land to be unable to be guaranteed and transferred. This caused losses for the Community and also for the parties who were affected by this problem. This research is a normative legal research. The results of this study are that the status of Freehold land of the Inhu Regency Community which is included in the forest area remains as Freehold land because no one has revoked its Ownership Rights. The Certificate of Ownership for land owned by the Community remains proof of legal and strong land ownership. The Inhu Regency Community cannot utilize their lands as the nature of Freehold land as a hereditary, strongest and most complete right. The material rights attached to the Freehold land have not been fulfilled. This shows the absence of certainty and legal protection for Freehold land holders in Indragiri Hulu Regency. Settlement of the status of Inhu Regency Community Land Rights that are included in the forest area, namely by removing the Land Rights from the forest area.